Effects of acidic and neutral biochars on properties and cadmium retention of soils. (August 2017) - Qi, Fangjie; Dong, Zhaomin; Lamb, Dane; Naidu, Ravi; Bolan, Nanthi S.; Ok, Yong Sik; Liu, Cuixia; Khan, Naser; Johir, M.A.H.; Semple, Kirk T.
Abstract: In this study, an acidic biochar and a neutral biochar were applied at 5 wt% into two soils for an 11-month incubation experiment. One Ferrosol soil (Ba) was slightly acidic with low organic matter and the other Dermosol soil (Mt) was slightly alkaline with high organic matter. The acidic (pH = 3.25) wood shaving (WS) biochar had no marked impact on nutrient levels, cation exchange capacity (CEC), pH and acid neutralization capacity (ANC) of either soil. By contrast, the neutral (pH = 7.00) chicken litter (CL) biochar significantly increased major soluble nutrients, pH, ANC of soil Ba. In terms of C storage, 87.9% and 69.5% WS biochar-C can be sequestrated as TOC by soil Ba and Mt, respectively, whereas only 24.0% of CL biochar-C stored in soil Ba and negligible amount in Mt as TOC. Biochars did not have significant effects on soil sorption capacity and sorption reversibility except that CL biochar increased sorption of soil Ba by around 25.4% and decreased desorption by around 50.0%. Overall, the studied acidic C rich WS biochar held little agricultural or remedial values but was favourable for C sequestration. The neutral mineral rich CL biochar may provide short-term agricultural benefit and certain sorption capacities of lower sorption capacity soils, but may be unlikely to result in heightened C sequestration in soils. This is the first study comprehensively examining functions of acidic and neutral biochars for their benefits as a soil amendment and suggests the importance of pre-testing biochars for target purposes prior to their large scale production. Highlights: The C rich acidic biochar did not work for nutrients supply or Cd retention but helped in storing C. The neutral mineral rich biochar enhanced nutrient and sorption for some soils. Neutral mineral rich biochar hardly increased soil C after 11 months.